Alteração estrutural e os produtos obtidos de povoamentos de Tectona grandis L.f. submetidos a desbastes - Alves, Viviann Maciel da Silva (2015)
The thinning is a forestry practice to reduce competition between individuals and restore growth of the remaining trees. The age at which trimming is applied, the type used and structural changes its intensity promote and improve the quality of the stand and tree volume. The objective of this study was to compare the structural change and the products obtained from stands of Tectona grandis subjected to selective thinning and mixed thinning. The study was conducted in two homogeneous and aged teak stands, planted with spacing of 3.0 m x 3.0 m, and chopped to five years of age. Permanent plots of 15m x 60m were established, 23 in Nossa Senhora do Livramento and 22 in São José dos Quatro Marcos, in them were measured total and commercial height and circumference at breast height and calculated the diameter at breast height, cross-sectional area, in addition to total and commercial volumes. The trees were still qualified on how to stem, as the healthy and determined the causes and extent of damage. For each installment, the individuals were still qualified as the dominance of certain class and the values of the same variables for each class. To compare products and structural changes of each of the thinning, the mean values of the plots were submitted to the Student test. With average values of parcels for dominance classes were made the horizontal and vertical profiles to schematically represent the structural change of thinned. The development of each of the thinned fifth grade was evaluated, and described independently to the sixth and seventh years. The type of applied thinning interferes with the quality of the remaining forest teak and products obtained from the operation. The mixed thinning removes top quality logs ace logs of selective thinning. The remaining trees mixed thinning an increased frequency of inferior individuals and alternating presence of lines with varying density. Selective thinning provides increased quality of the remaining trees, with a better performance in relation to mixed thinning, even in the first year to present higher development compared to selective.